Improving Literature and Numeration In Elementary School Learning Activities And Increasing Community Income That Comes From Oil Palm In Village Mata PAO - Indah Permata Sari (Journal of Community Service For Indonesian Society, 2023)
Community service activities aim to significantly improve literacy and numeracy in learning activities and increase community income. This community service is a mentoring activity carried out by students through literacy and numeracy schemes in elementary schools. This activity was carried out for 21 days, starting from August 11, 2022 – August 31, 2022. Community service has a goal, namely to provide experience for students to be directly involved in implementing the learning process at school. The method used in the implementation of this Independent Real Work Lecture is the method of observation, interviews and documentation. Activities carried out by students with assistance include: (1) introduction in the village; (2) introduction to the scope of the school; (3) support the class in the development of literacy and numeracy learning; (4) assisting the community to increase income derived from oil palm fronds. Service activities carried out by students through community service assistance with literacy and numeracy program schemes as well as helping the community have been running well, efficiently, effectively and maximally. The results of this study after doing research that the interest of students in literacy and numeracy factors is good with the implementation of learning outside the classroom while playing and the income function of the community has also increased from the use of palm oil sticks which are used in making various kinds of handicraft products that have functional values.